The great fire - Hazzard , Shirley 1931-2016. (Virago, 2003)
The year is 1947. The great fire of the Second World War has convulsed Europe and Asia. In its wake, Aldred Leith, an acclaimed hero of the conflict, has spent two years in China at work on an account of world-transforming change there. Son of a famed and sexually ruthless novelist, Leith begins to resist his own self-sufficiency, nurtured by war. Peter Exley, another veteran and an art historian by training, is prosecuting war crimes committed by the Japanese. Both men have narrowly escaped death in battle, and Leith saved Exley's life. The men have maintained long-distance friendship in a postwar loneliness that haunts them both, and which has swallowed Exley whole. Now in their thirties, with their youth behind them and their world in ruins, both must invent the future and retrieve a private humanity.Arriving in Occupied Japan to record the effects of the bomb at Hiroshima, Leith meets Benedict and Helen Driscoll, the Australian son and daughter of a tyrannical medical administrator. Benedict, at twenty, is doomed by a rare degenerative disease. Helen, still younger, is inseparable from her brother. Precocious, brilliant, sensitive, at home in the books they read together, these two have been, in Leith's words, delivered by literature. The young people capture Leith's sympathy; indeed, he finds himself struggling with his attraction to this girl whose feelings are as intense as his own and from whom he will soon be fatefully parted.